The Institution of Theory - Krieger, Murray (Johns Hopkins University Press, 2019)
Originally published in 1994. In The Institution of Theory, Murray Krieger examines, at once sympathetically and critically, the process by which theory has become institutionalized in the American academy and the consequences of theory as an academic institution. He traces the transformation of literary theory into critical theory and relates it to changes in the place of literature within questions about discourse at large. And he faces the costs as well as the gains of the recent denial of privilege to the literary. To support his view of the issues at stake in current theoretical debates, Krieger surveys both the history of American criticism and the general history of literary theory in the West. He sees divisions in each of them that foreshadow the current debates: in the first a conflict between the social and the aesthetic functions of literature, and in the second a conflict between the treatment of literature as a reflection of a culture's ideology and the treatment of literature as a subversion of that ideology. To what extent, he asks, are our debates new and to what extent are they merely refashioned versions of those we have always had?